STUDYING RISK FACTORS IN THE DEVELOPMENT OF PSYCHOGENIC DEPRESSIONS OF THE INVOLUTIONARY PERIOD (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Last decades approaches to an assessment of an outcome of depressive distress at persons of serotinal age have undergone essential changes. Along with conservation of traditional methodology in definition of categories of an outcome of depression and their division into the congenial and unfavorable bunches (Jhingan H.P., Sagar R., 2001; Baldwin R.CandGallagley A., 2006), representation about criteria of reference of each concrete variant of an outcome to one of these categories has extended.